Relationship Model of Competitiveness and Productivity of Engineering Procurement and Construction for Indonesia Construction Industry - Mairizal; Taufik, Agus (International Journal of Sustainable Construction Engineering and Technology, 2023)
The need for EPC Contract Work Services is increasing along with economic development and infrastructure needs in Indonesia. For the success of EPC, the productivity of EPC companies and their competitiveness are very much needed. This study aims to determine the factors of competitiveness that affect the productivity of companies and their people. In addition, this study also intends to find out the factors that affect the productivity of internal parts and investigate the model of the relationship between competitiveness and productivity. Collecting data is quantitative by distributing questionnaires to several 20 respondents. Data analysis was carried out in 4 (four) stages, namely data collection, data reduction, data presentation, and drawing conclusions. The data analysis process was carried out using SPSS and Smart PLS software. The results of this study are believed to be able to add to the knowledge base, especially in the field of employee productivity development for EPC companies in Indonesia. The findings obtained from this study state that factor analysis shows the factor of Competitiveness (Independent Variable) is influenced by Appreciation of Criticism (X11), Oral Communication (X8), Performance Theory (X3), Personality Theory (X2), Problem Analysis Skills (X6) , Integrity (X15), Team Collaboration Skills (X10), Engagement (X13), Customer Orientation (X14), Observation Skills (X7), Openness to Criticism (X12) and Writing Skills (X9). While Productivity (Y) is strongly influenced by Labor (Y1) and Materials (Y2).